COACHING MODULE DEVELOPMENT TO BECOME TOUGH PERSONS FOR SIXTH-GRADE ELEMENTARY STUDENTS (BASED ON IGNASIAN SPIRITUALITY) - Sumarah, Ignatia Esti; Utama, Ignatius Loyola Madya; Setyawan, Yustinus Budi (Sanata Dharma University Yogyakarta, 2022)
From the results of pre-study questionnaires distributed to seventeen sixth-grade elementary students of SD Sanjaya Tritis Pakem District and SD Cahaya Bangsa Utama Yogyakarta, researchers obtained data that they had difficulty concentrating in learning because they prefer to play games. In fact, they will face the Regional Education Standardization Assessment (ASPD). Researchers were encouraged to help them doing mindfulness exercises so that they can exercise self-control when facing difficulties or temptations, with the guidance of “Becoming a tough person based on Ignatian Spirituality” module developed by the researchers. The development of the coaching module was carried out by researchers using the five-step ADDIE model, namely: (1) Analysis: distributing questionnaires to obtain information about the duration of time the sixth-grade elementary students spent to study and play games; (2) Design: compiling a grid of coaching modules. (3) Development: compiling a coaching module which then validated by a lecturer and teacher. The average score of the two validators showed a good result, which is 3.4 (from a range of values 1-4), meaning that the coaching module can be tested and published. (4) Implementation: the researchers conducted a trial at SD Sanjaya Tritis Pakem District which was attended by 15 students. (5) Evaluation: from the results of reflection, the students wrote down their intentions to manage the desire to play so they can focus on learning.